PENERAPAN VIDEO PEMBELAJARAN MENGGUNAKAN APLIKASI CANVA UNTUK MENCIPTAKAN LINGKUNGAN BELAJAR YANG MENYENANGKAN PESERTA DIDIK KELAS IX SMP NEGERI 7 PALEMBANG - Sapna Sapira; Juaidah Agustina (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to explore the application of learning videos using the Canva application in creating a pleasant learning environment for class IX students at SMP Negeri 7 Palembang. This research uses a qualitative descriptive approach. This approach focuses on collecting qualitative data through observation and recording. The data sources used in this research are 1) the events observed were the process of implementing learning by implementing animated learning videos using the Canva application, 2) documents in the form of open modules, 3) field notes obtained through observation. The research results show increased motivation and engagement of students during the learning process. In addition, feedback from participants indicated that the use of interesting learning videos could improve understanding of the material and create a more positive learning atmosphere. This research concludes that the application of learning videos using Canva is effective in creating a pleasant learning environment and can be used as an alternative to improve the quality of learning in the classroom.